Blessed Louis, the most glorious of kings texts relating to the cult of Saint Louis of France - Gaposchkin, M. Cecilia 1970- (Notre Dame texts in medieval culture, 2012)
Intro -- Contents -- Preface and Acknowledgments -- Abbreviations -- Manuscript Sigla -- Introduction -- Chapter 1: Gloriosissimi Regis -- Chapter 2: Beatus Ludovicus -- Chapter 3: Office and Mass Texts -- Chapter 4: Sermons of Jacob of Lausanne -- Bibliography.